Musical Composition Jurung-Jurung | Komposisi Musik Jurung-Jurung - Suradinata, I Kadek Bagas; Sudirga, I komang (Pusat Penerbitan LPPMPP ISI Denpasar, 2024)
This article refers to the lack of literacy regarding the Jegog Jembrana gamelan in terms of musicality. The Jegog Jembrana gamelan has many techniques, one of which is the jurung-jurung technique. The jurung-jurung or transition technique is one of the stylists' interests in creating a new work. Jurung-jurung is one of the Jegog techniques, which means types of transitions in classical Jegog compositions and not all classical Jegog percussion transitions have the Jurung-jurung technique, but they are in accordance with the classical composition of Jegog percussion. The method I use is based on the creation method according to Alma. M Watkins namely exploration, improvisation, and formation. This method is very influential in making this composition because the stages are simple and easy to understand. The relevance of this work will be very useful for the community and artists who want to develop Jegog Jembrana art.